A disaggregated view of soft skills: Entrepreneurship education systems of Africa - Paul Jones (Journal of Small Business Management, 2024)
Much of the literature on entrepreneurship education describes the teaching concept as a whole, which means that additional work must be done to tease out its individual components. Accordingly, this study focuses on soft skills—a core component of entrepreneurship education that represents entrepreneurial behaviors, attitudes, and attributes. It examines the mechanisms underlying soft skills and entrepreneurial readiness by drawing on a mediated model of entrepreneurship education and 300 observations on aspiring South African entrepreneurs. Regression tests reveal that while soft skills determine the entrepreneurial readiness of these entrepreneurs, their impact on their ability to start, innovate, finance, and grow new ventures is mediated by the entrepreneurial processes that define their entrepreneurial journeys. This has academic, policy, and social implications as it increases the importance of developing contextual insights into the facets of soft skills in an African country to inspire policy reforms that support African entrepreneurship.